When the world loved the Filipinos and other essays on Philippine history - Dery, Luis Camara (Manila UST Pub. House, 2005)
"The essays focus on different topics about Philippine history. They show different threads that compose the Philippine past and at the same time highlight the many experiences of the Filipino people through the centuries of their existence. They demonstrate the developments that occurred in the country brought about by the interplay of external stimuli. These many developments and variations in the historical development of the country and its inhabitants substantiate the idea that history is not only an interesting field of study but is also an inexhaustible reservoir of lessons from which the Filipino people could draw upon as they face the many uncertainties of the future."--Introduction.
When the world loved the Filipinos : foreign freedom fighters in the Filipino army during the Filipino-American War -- Acta de Capitulaciones : Filipino victories against the Spaniards and Americans during the revolution -- Principales y conquistadores : why it took the Filipinos so long to end Spanish domination -- The hand that rocks the cradle : rediscovering the images of womanpower in Philippine history -- From the Moluccas to the Philippines : the diaspora of the Mardicas of Ternate, Cavite -- General Jose Ignacio Paua and his role during the Philippine revolution -- The soul of 1896 : the truth about the Katipunan and the Philippine national flag -- The Tagalog Christ : Dr. Jose P. Rizal beyond A.D. 2000.
Keywords: Philippines -- History